The Influence of Accountability and Transparency on the Quality of Public Services of the Investment and One-Stop Integrated Licensing Service Office of Binjai City - Ardia Theresia Br Pasaribu; Galih Supraja (CV. AFDIFAL MAJU BERKAH, 2025)
This study is entitled